Lecturas contemporáneas de la ley natural - Donadío Maggi de Gandolfi, María C. (Sapientia, 2013)
the natural Law theory has had a great development in Ethics, beyond its legal framework, so we can truly speak of a Natural Law Ethics, in full validity from its born in the Greek through the contemporary philosophy. In this paper, I address the special readings of the Neo-analytical moralists of English language, who deal, systematic and/or historically, with the natural law’s question. They sometimes translate the natural law to its own epistemology, either in confrontation or critically, or in a «sui generis» recognition. This allows us to talk about a full validity of the significance of its concept: to be a law that has its support in the rational and universal nature of mankind